STUDI LITERASI: PERBEDAAN MORFOLOGI KOPI ARABIKA DAN KOPI ROBUSTA - Ameilia Zuliyanti Siregar; Gusti Setiavani; Addiena Kinanthi Alfiah; Deo Elfriadi Pane; Diva Rifany Lubis; Erlikasna Br Surbakti; Gerhat Cahyono Hutapea; Hayati Maidah Padang (PT. Intelek Cendikiawan Nusantara, 2025)
This study aims to synthesize the morphological differences between Arabica and Robusta coffee and their implications for productivity, bean quality, and farmer empowerment through a literature review approach. A total of 25 scientific sources were analyzed, consisting of 15 experimental and 10 non-experimental studies that examined root, stem, leaf, flower, fruit, and seed characteristics, as well as their relationships with physical–chemical properties and cup quality. Data from each journal were traced based on objectives, methods, locations, and main findings, then processed descriptively and comparatively to identify consistent patterns of similarity and difference between the two coffee species. The review shows that Robusta generally has higher vigor, larger stems, thicker leaves, and denser canopies, making it more adaptive to lowland and hot–humid environments, whereas Arabica tends to have a more compact canopy and larger, more elongated beans associated with more complex sensory quality. Differences in seed morphology are accompanied by variation in chemical composition such as caffeine, chlorogenic acids, sugars, and lipids, which shape taste profiles and market segments. Structured morphological information is therefore important as a basis for field identification, genetic diversity mapping, planting material selection, and the development of extension materials and Good Agricultural Practices (GAP) tailored to specific locations for Arabica and Robusta coffee farmers.